2022
DOI: 10.1111/jipb.13353
|View full text |Cite
|
Sign up to set email alerts
|

BioClay™ prolongs RNA interference‐mediated crop protection against Botrytis cinerea

Abstract: One of the most promising tools for the control of fungal plant diseases is spray‐induced gene silencing (SIGS). In SIGS, small interfering RNA (siRNA) or double‐stranded RNA (dsRNA) targeting essential or virulence‐related pathogen genes are exogenously applied to plants and postharvest products to trigger RNA interference (RNAi) of the targeted genes, inhibiting fungal growth and disease. However, SIGS is limited by the unstable nature of RNA under environmental conditions. The use of layered double hydroxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 34 publications
(58 reference statements)
0
24
0
Order By: Relevance
“…This is similar to the extended protection provided by inorganic dsRNA complex formulations against viruses on Nicotiana tabacum cv. Xanthi leaves and fungal pathogens on tomato plants 27,34 . Another key advantage of utilizing liposome technology for crop protection, especially post-harvest products, is that the success of similar formulations in clinical applications 47 suggests that the AVs will be safe for human consumption.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is similar to the extended protection provided by inorganic dsRNA complex formulations against viruses on Nicotiana tabacum cv. Xanthi leaves and fungal pathogens on tomato plants 27,34 . Another key advantage of utilizing liposome technology for crop protection, especially post-harvest products, is that the success of similar formulations in clinical applications 47 suggests that the AVs will be safe for human consumption.…”
Section: Discussionmentioning
confidence: 99%
“…These studies demonstrate crosskingdom RNAi is a conserved mechanism across different species, including plant and animal hosts. Consequently, SIGS RNAs which target genes involved in RNAi machinery and in sRNA biogenesis have proven to be quite effective [7][8]10,23,[25][26][27][28] , making them ideal biological pathways to target in other organisms. Furthermore, because RNAi can tolerate multiple mismatches between sRNAs and target RNAs 29 , fungal pathogens are less likely to develop resistance to SIGS RNAs than to traditional fungicides, which mostly bind to and inhibit a specific enzyme or protein.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanoparticle-cargo conjugates can be delivered through leaf infiltration using a needless syringe in a lab research context, and for scalable field applications, there are some studies demonstrating the feasibility of topical application of doublestranded RNA (dsRNA) and siRNA cargoes with layered double hydroxide (LDH) nanoparticles (Mitter et al, 2017) and carbon dots (Schwartz et al, 2020) (Figure 1D), which eliminates the issues of the instability of naked RNA sprayed on plants. The LDH platform, which is called BioClay, enabled virus/fungus protection for 21 days when sprayed on virus/fungus-challenged leaves (Mitter et al, 2017;Niño-Sánchez et al, 2022). More recently, the BioClay technology has been topically applied for dsRNA delivery into tomato pollen (Yong et al, 2021), extending the plant tissue types for various applications.…”
Section: Nanoparticle-based Gene Delivery Methodsmentioning
confidence: 99%
“…42,[74][75][76] Notably, Worrall et al 74 observed inhibition of aphid-mediated virus transmission between plants after spraying dsRNA-BioClay (dsRNAloaded, biodegradable, layered double hydroxide clay nanosheets) targeting a plant virus. More recently, Jain et al 42 demonstrated the capacity of dsRNA-BioClay in protecting sprayed plants from all life stages of the whitefly B. tabaci, and Niño-Sánchez et al 77 demonstrated prolonged plant protection against Botrytis cinerea Pers., using dsRNA-BioClay spray, compared to naked dsRNA. DsRNA-BioClay spray technology is currently being further developed through a partnership between the agricultural chemical company Nufarm (Melbourne, Australia) and the University of Queensland.…”
Section: Recent Achievements Transferable To Rna-based Protection Of ...mentioning
confidence: 99%